PEMBELAJARAN MENULIS TEKS PROSEDUR MENGGUNAKAN METODE PICTURE AND PICTURE PADA KELAS XI - Ineu Nurjanah; Taufik Aji Darma; Yeni Rostikawati (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2019)
This research is motivated by the existence of data from the evaluation results on the writing skills of students in class XI tend to be still low. This is caused by the selection of learning methods used less suitable with the material being taught, so students experience difficulties and are less motivated during learning. Based on the description, the study of learning to write text procedures was carried out using the Picture and Picture method in students of class XI Vocational School. The purpose to be obtained is to find out the results of student writing using the Picture and Picture method and to find out the differences in the learning outcomes of writing Procedure Text using the Picture and Picture method. This research uses Pre-Experimental Design research method with One Group Pre-Test Post-Test Design approach. The researcher chose 30 students in the XI class. The researcher carried out data collection techniques by conducting the initial test (pretest) and the final test (posttest). Based on the results of the test, the average pretest value was 52 and the posttest average value was 78.5 so that it showed the difference results with a difference of 26.5.